Implementation of Techniques of Soft Computing on Bio Medical Image Processing - Narayan Mohanty, Mihir; Prasad Mishra, Laxmi (International Journal of Psychosocial Rehabilitation, 2025)
this paper proposes a solution to those real world problems that cannot be solved mathematically by soft computing. It enables solution to ambiguous problems by a fusion of methodologies. Soft computing comprise of complementary elements of fuzzy logic, evolutionary computation and neural computing. Applications of soft computing are found in various areas, most importantly image processing. Applications of different methods of soft computing are found in biological and industrial processes, financial and investment trading and engineering design. The literature is analysed based on the style of method of soft computing, the discipline of investment used, and demonstration of success and application of research in real world problems.